When Athens met Jerusalem an introduction to classical and Christian thought - Reynolds, John Mark, 1963- (Downers Grove, Ill. : InterVarsity Press, 2009)
Christian theology shaped and is shaping many places in the world, but it was the Greeks who originally gave a philosophic language to Christianity. John Mark Reynolds's book When Athens Met Jerusalem provides students a well-informed introduction to the intellectual underpinnings (Greek, Roman and Christian) of Western civilization and highlights how certain current intellectual trends are now eroding those very foundations. This work makes a powerful contribution to the ongoing faith versus reason debate, showing that these two dimensions of human knowing are not diametrically opposed, but work together under the direction of revelation. - Publisher.
Introduction : Athens and Jerusalem -- Building Athens : philosophy before Socrates -- The death of a good man -- The ideal philosopher : Plato and his teachings -- Follow the logos wherever it leads : what is a dialogue? -- In love with the good -- The city in words : on justice -- The likely story : the Timaeus -- Breaking with the Master : Aristotle and the "other" path -- The middle way : Aristotle's ethics -- Preparing the way for Christ : Hellenistic philosophy -- A postscript : where do we go from here?
Includes bibliographical references and index.
Description based on print version record.
Keywords: Christianity -- Origin; Philosophy, Ancient; Christianity -- Philosophy; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books